Case Report: The Role of Neuropsychological Assessment and Imaging Biomarkers in the Early Diagnosis of Lewy Body Dementia in a Patient With Major Depression and Prolonged Alcohol and Benzodiazepine Dependence - Bouter, Caroline; Hansen, Niels; Timäus, Charles; Wiltfang, Jens; Lange, Claudia (Frontiers in Psychiatry, 2020)
Dementia with Lewy bodies (DLB) is the second most common form of dementia and is assumed to be often under- or misdiagnosed, especially in early stages. Here we present a complex case of probable DLB with major depression and alcohol and benzodiazepine dependence in which DLB was ruled out initially. This case highlights the challenging diagnostic workup of DLB patients. Core clinical features can be missing and indicative biomarkers can be negative, especially in early stages of the disease. Initially, Fluorodeoxyglucose positron emission tomography as well as neuropsychological assessment were suspicious for a possible DLB diagnosis in our patient while core clinical criteria were missing and the indicative biomarker 123I-FP-CIT SPECT was negative. Follow up was performed two years later and the patients showed several core and supportive clinical features of DLB and 123I-FP-CIT SPECT showed a pathological pattern. Extensive neuropsychological assessment in combination with PET imaging might provide crucial evidence for DLB even in early stages. If neuropsychology and PET imaging point to an early DLB diagnosis careful follow-up should be performed as core symptoms and indicative biomarkers might appear in later stages of the disease.